Service Management The New Paradigm in Retailing - Kandampully, Jay.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
TK
Keywords: Economics; Industrial management; Marketing; Economics/Management Science; Marketing; Management/Business for Professionals; Production/Logistics/Supply Chain Management